A 46-inch diagonal carbon nanotube field emission backlight for liquid crystal display. (September 2015) - Kim, Yong Churl; Park, Shang Hyeon; Lee, Chang Soo; Chung, Tae Won; Cho, Eunseog; Chung, Deuk Seok; Han, In Taek
Abstract: A large area carbon nanotube field emission backlight that is built with a new cathode structure is reported. The approach involves unique gate insulator formation by glass etching, highly populated multi wall nanotube tips, and gate electrode assembly by anodic bonding. Impressive lamping performances are noted through dynamic control of the built in fine 4320 local dimming blocks as small as 1 cm 2 . The liquid crystal display lit by the backlight demonstrates superior luminance uniformity 97%, and a native contrast ratio 400, 000:1, whilst showing less than 10% decay in emission current of the sealed panel during continuous operation over 8000 h.